Quantitative Electromyographic Analysis of Reaction Time to External Auditory Stimuli in Drug-Naïve Parkinson’s Disease - Do-Young Kwon; Byung Kyu Park; Ji Won Kim; Gwang-Moon Eom; Junghwa Hong; Seong-Beom Koh; Kun-Woo Park (Parkinson's Disease)
Evaluation of motor symptoms in Parkinson’s disease (PD) is still based on clinical rating scales by clinicians. Reaction time (RT) is the time interval between a specific stimulus and the start of muscle response. The aim of this study was to identify the characteristics of RT responses in PD patients using electromyography (EMG) and to elucidate the relationship between RT and clinical features of PD. The EMG activity of 31 PD patients was recorded during isometric muscle contraction. RT was defined as the time latency between an auditory beep and responsive EMG activity. PD patients demonstrated significant delays in both initiation and termination of muscle contraction compared with controls. Cardinal motor symptoms of PD were closely correlated with RT. RT was longer in more-affected side and in more-advanced PD stages. Frontal cognitive function, which is indicative of motor programming and movement regulation and perseveration, was also closely related with RT. In conclusion, greater RT is the characteristic motor features of PD and it could be used as a sensitive tool for motor function assessment in PD patients. Further investigations are required to clarify the clinical impact of the RT on the activity of daily living of patients with PD.